1978
DOI: 10.1044/0161-1461.0901.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Articulation and Syntax Programs on Syntax and Articulation Improvement

Abstract: This study investigated the influence of interventive programs for syntax and articulation on the articulatory and syntactic skills of public school children with multiple-linguistic problems. One group received a program of syntax exclusively, a second received a program of articulation exclusively, and a third received no intervention. Pre- and posttesting revealed that the two experimental groups made significant gains in both syntax and articulatory skills, while the control subjects made no significant ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 0 publications
1
35
1
1
Order By: Relevance
“…Some are theoretical. For instance, Matheney and Panagos (1978) found that therapy for grammar improved articulation (and vice versa). This result was not replicated in Fey et al (1994).…”
Section: Two Decades Of Troublesome Trialsmentioning
confidence: 99%
“…Some are theoretical. For instance, Matheney and Panagos (1978) found that therapy for grammar improved articulation (and vice versa). This result was not replicated in Fey et al (1994).…”
Section: Two Decades Of Troublesome Trialsmentioning
confidence: 99%
“…Only Johnson and Thomas (1995) reported outcomes for receptive language. Methany and Panagos (1978) carried out an RCT to compare the effects of (Gray and Ryan 1973). Clinical Evaluation of Language Fundamentals (Revised) (Semel and Wiig 1987).…”
Section: Research Literaturementioning
confidence: 99%
“…Ten RCTs and 12 controlled studies were identified which evaluated treatment, mostly for problems of articulation or phonology and expressive language. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] These studies show that interventions are eVective in enhancing speech, expressive language, receptive language, and auditory discrimination relative to untreated controls. The size of the benefits represented progress from the 5th to the 25th percentile on a norm-referenced test.…”
Section: Delaymentioning
confidence: 99%